Analisis Yuridis Perjanjian Kerja Waktu Tertentu Menurut Hukum Ketenagakerjaan Indonesia - Oktavia Eko Anggraini (Eastasouth Institute, 2022)
In Law Number 13 of 2003, Chapter 1 Article 1 Paragraph (2) concerning Manpower which states that a manpower is anyone who is able to do work to produce goods and/or services both to meet his own needs and for the community. The problem in this research is how is the legal protection of PKWT according to Indonesian labor law and what about legal protection for workers whose work agreement period is not in accordance with the provisions of the legislation. This research method uses a normative juridical approach, with secondary data collection, to prove the legal protection of PKWT according to labor law. The data obtained were analyzed qualitatively. Based on the results of the study, it was found that the Employment Law on Specific Time Work Agreements was more beneficial to the company. In a Specific Time Work Agreement according to the Manpower Law, workers/labourers get legal protection as long as the working period is still valid, in accordance with the Manpower Act.